2004
DOI: 10.1002/ijc.20460
|View full text |Cite
|
Sign up to set email alerts
|

Prostate carcinoma and green tea: PSA‐triggered basement membrane degradation and MMP‐2 activation are inhibited by (−)epigallocatechin‐3‐gallate

Abstract: Prostate-specific antigen (PSA) is a serine-protease that, in addition to cleaving semenogelins in the seminal coagulum, is able to cleave extracellular matrix glycoproteins, thereby affecting cell migration and metastasis. We here report some new activities of PSA that deserve careful consideration in the cancer context: degradation of gelatin, degradation of type IV collagen in reconstituted basement membrane (Matrigel) and activation of progelatinase A (MMP-2), but not pro-MMP-9, in a cell-free system. Sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…This hypothesis is supported by the finding that EGCG inhibited metallo-proteinase-2 and reduced basement lamina degradation in prostate carcinoma cells (Pezzato et al 2004). In addition, EGCG has been demonstrated to possess potent antimatrix metalloproteinase activity in cancer cell cultures, also blunting the angiogenesis crucial for the growth of solid tumours (Garbisa et al 1999;Maeda et al 2003).…”
Section: Discussionmentioning
confidence: 73%
“…This hypothesis is supported by the finding that EGCG inhibited metallo-proteinase-2 and reduced basement lamina degradation in prostate carcinoma cells (Pezzato et al 2004). In addition, EGCG has been demonstrated to possess potent antimatrix metalloproteinase activity in cancer cell cultures, also blunting the angiogenesis crucial for the growth of solid tumours (Garbisa et al 1999;Maeda et al 2003).…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, ET-1 contributes to the acquisition of migratory and invasive phenotype by inducing the disruption of host-tumor interactions (36) and by up-regulating protease (6) and VEGF expression (8,9,13,14). Green tea polyphenols are becoming increasingly recognized for their antiangiogenic, antimetastatic (17,18), and anti-invasive properties as potent inhibitors of VEGF production (32) and MMPs, such as MMP-2 and MMP-9, in different cell types (25,37). Studies have shown that polyphenols from green tea possess antitumor and antimetastatic activity in animal xenograft and allograft model, suggesting a possible therapeutic potential (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In androgen-dependent (androgen receptor positive) LNCaP cells, EGCG contributed to anti-invasive and anti-migratory effects via the downregulation of androgen-induced uPA, MMP-2/MMP-3/MMP-9, VEGF, and Ang1/2 and upregulation of TIMP-1 [96,97]. Furthermore, EGCG inhibited the PSA-triggered basement membrane degradation and MMP-2 in Du145 and LNCaP cells [98] as well as inflammation-triggered MMP-2; invasion of mouse prostate (TRAMP)-C1 cells in transgenic adenocarcinoma has also been demonstrated [99]. These results indicated that EGCG could synergistically inhibit biomarkers associated with angiogenesis and metastasis of prostate carcinoma.…”
Section: Egcg Egc Ecg and Ecmentioning
confidence: 99%